Cold feet [large type] : a Stella Lavender mystery - Pullen, Karen (A Stella Lavender mystery, 2013)
Special Agent Stella Lavender has a stressful, adrenaline -fueled job: buying drugs undercover from paranoid drug dealers. So she's grateful to spend an afternoon relaxing at an elegant outdoor wedding. But as the guests grow restive, the satin-clad bride is dying most horribly. Who would kill a bride - an "angel" according to her groom - minutes before her nuptials? Joining the investigation, Stella must untangle a complex knot of secrets in order to find a killer.